Adjusting device for AGV (Automatic Guided Vehicle) - ZHU WEI; SHI SHENGXIANG; XU NAIQING; HUA YUNFENG; XU WEI (2024)
The invention belongs to the technical field of part transportation, and discloses an adjusting device for an AGV. The device comprises a tray assembly and adjusting assemblies, the tray assembly is installed on an AGV trolley, a gap is formed between the adjusting assemblies, the AGV trolley is stopped in the gap, the tray assembly comprises an upper tray and a lower tray, the lower tray is fixed to the AGV trolley, the upper tray is connected with the lower tray through a spring piece, and a first limiting column is installed on the upper side of the upper tray; the adjusting assembly comprises a first air cylinder, the first air cylinder pushes a first pushing block to move, the first pushing block abuts against the first limiting column, an inserting groove is formed in the lower side of the upper tray, a second air cylinder is installed on the adjusting assembly, the second air cylinder pushes a lifting block in the jacking mechanism to move perpendicular to the horizontal plane, and the lifting block is